2009
DOI: 10.2337/dc09-1890
|View full text |Cite
|
Sign up to set email alerts
|

Brief Screening Tool for Disordered Eating in Diabetes

Abstract: OBJECTIVETo update and validate a diabetes-specific screening tool for disordered eating (the Diabetes Eating Problem Survey [DEPS]) in contemporary youth with type 1 diabetes.RESEARCH DESIGN AND METHODSA total of 112 youth with type 1 diabetes, ages 13–19 years, completed the DEPS. Higher scores on the DEPS indicate more disordered eating behaviors. Youth and their parents also completed additional surveys to examine diabetes-specific family conflict, negative affect related to blood glucose monitoring, youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
255
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(283 citation statements)
references
References 22 publications
18
255
0
10
Order By: Relevance
“…1,2,[25][26][27] Other studies involving individuals with T1D, however, have not found such differences.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1,2,[25][26][27] Other studies involving individuals with T1D, however, have not found such differences.…”
Section: Discussionmentioning
confidence: 89%
“…Although other instruments specific to the investigation of risk behavior for ED in patients with T1D are available, none have been translated into Portuguese or validated for Brazil. [25][26][27] It bears noting that certain items of standardized tests, instead of representing risk behavior for ED, could rather be seen as indicating adequate control of diabetes. 9,33 This could be the case for EAT items such as ''I eat diet foods,'' ''I avoid foods with sugar in them,'' and ''I particularly avoid foods with a high carbohydrate content.''…”
Section: Limitationsmentioning
confidence: 99%
“…The majority of the items on the DEPS-R were endorsed less frequently from baseline to the 1-month and 6-month follow-up assessments. Compared with a previous 11 sample of youth with T1D, 13-19 years old, baseline DEPS-R scores in this sample were slightly lower (median, 9.8 vs. 8.0), although the range was wider (range, 4.0-13.0 vs. 0-52.0). This may be due to the wider age range of the current sample (10-17 years) and their shorter diabetes duration compared with the earlier group.…”
Section: Eating Behaviors In Youth With T1dmentioning
confidence: 93%
“…Disordered eating behavior was assessed using the 16-item Diabetes Eating Problem Survey (DEPS-R) (Markowitz et al, 2010). The survey assesses behaviors such as skipping insulin or keeping blood sugars high to lose weight as well as feelings towards the relative priorities of losing weight and taking care of one’s diabetes.…”
Section: Methodsmentioning
confidence: 99%